Radical uncertainty decision-making beyond the numbers - Kay, John 1948-; King, Mervyn 1948- (W.W. Norton & Company, 2021)
"In a changing world, forecasts and numbers usually represent bogus quantification. Kay and King tell us how to think smarter. Radical uncertainty changes the way we should think about decision-making. For over half a century economics has assumed that people behave rationally by optimizing among well-defined choices. Behavioral economics questioned how far people are rational, pointing to the cognitive biases that seem to describe actual behavior. Radical Uncertainty is a bold, paradigm-shifting book that takes us past standard and behavioral economics, completely shifting our understanding of the role economics can play in decision-making. We can never have the information required to optimize. But the failure to come to terms with this reality has led us to build our largest financial organizations, develop major policy decisions, and create business structures on shifting sands-the false belief that the numbers provided by economic models give us the answer. They don't. The best managers in the public and private sectors rely on narratives, not numbers"--
Keywords: Wirtschaftswissenschaften; Unsicherheit; Entscheidungsfindung; Economics / Psychological aspects; Consumer behavior; Decision making / Economic aspects